Effect of drain‐blocking and meteorological factors on ground water table fluctuations in Kamanos mire - Ruseckas, Juozas; Grigaliūnas, Vaidotas (Journal of Environmental Engineering and Landscape Management, 2008)
The study was carried out in a raised bog located in the Kamanos state reserve in northwestern Lithuania (56°16’N, 22°39’W). The area of the raised bog is 1722 ha. To assess the effect of meteorological factors and damming of drainage ditches on the water regime of the Kamanos mire, we have analysed the water table depth fluctuations over the last 22 years in the northern part of the mire, which was drained out in 1907, and the drainage ditch was dammed in 1999. The control plots were established in the central part of the raised bog without draining activities, where Eriophorum va‐ginatum‐Sphagnum spp. communities prevail in the ground vegetation and small Scots pine trees may also be found. The results showed that, in both natural and damaged‐by‐drainage sites of the raised bog, the air moisture deficiency and the amount of precipitation had a significant effect on the fluctuation of the water table depth during the growth period (R = 0.416 ‐ 0.761 p < 0.05). In comparison with the control plots, in 7 years after establishing dams in a 0.9–1.2 m deep ditch, the groundwater table increased by 9.8 to 12.2 cm in the area up to 980 m apart from the ditch. After damming the ditches in the extensively and intensively drained parts of the raised bog, the levelling out of the water table to a similar depth as in the control plots, occurred within 4 years and is forecasted to occur within 12 years, respectively. The water table of the drained sites of the raised bog was more sensitive to increasing annual temperatures than the water table in the undrained sites of the raised bog. Griovių blokavimo bei meteorologinių faktorių įtaka kamanų pelkės gruntinių vandenų slūgsojimo lygio svyravimams Santrauka. Tyrimai buvo atlikti Kamanų valstybinio gamtinio rezervato aukštapelkėje (56º16´N, 22º39´W), kuri yra šiaurės vakarų Lietuvoje. Aukštapelkės plotas – 1722 ha. Tam, kad būtų įvertinta meteorologinių faktorių bei griovių tvenkimo įtaka Kamanų pelkės hidrologijai, buvo išanalizuotos gruntinių vandenų slūgsojimo lygio fluktuacijos per pastaruosius 22 metus – 1907 m. nusausintoje ir 1999 m. patvenktoje šiaurinėje pelkės dalyje. Kontroliniai plotai išskirti centrinėje nesausintoje aukštapelkės dalyje. Čia vyrauja Eriophorum vaginatum-Sphagnum spp. (kupstinio švylio-kiminų) bendrijos su žemaūgėmis pušelėmis. Nustatyta, kad pagrindiniai meteorologiniai veiksniai, veikiantys vegetacijos periodo gruntinių vandenų fluktuacijas tiek natūraliuose, tiek sausinimu pažeistuose Kamanų aukštapelkės plotuose, yra oro drėgmės deficitas ir krituliai (R 2 = 0,416 – 0,761 p < 0,05). Per 7 metų periodą, praėjusį po 0,9–1,2 m gylio griovio, sausinusio aukštapelkę 92 m. blokavimo užtvaromis (1999 m.), gruntinių vandenų lygis 980 m pločio pagriovio zonoje, palyginus su kontrole, pakilo vidutiniškai 9,8–12,2 cm. Gruntinių vandenų atsistatymas iki kontrolinio lygio, blokavus griovius užtvaromis ekstensyviai nusausintose pelkės dalyse, įvyko per 4 metus, o intensyviai nusausintoje aukštapelkės dalyje, kaip rodo prognozės, įvyks apytiksliai per 12 m. Išaiškinta, kad į klimato šiltėjimą, t. y. į metinių temperatūrų didėjimą, nusausintų pelkių gruntiniai vandenys reaguoja labiau negu nenusausintų. Reikšminiai žodžiai: gruntinio vandens lygis, griovių blokavimas užtvaromis, hidrologija, meteorologiniai veiksniai, pelkė. Влияние изменения климата и уничтожения канав на гидрологический режим болота Каманос Резюме. Гидрологические исследования были проведены на верховом болоте государственного заповедника Каманос (56º16´N, 22º39´W), который находится на северо-западе Литвы. Площадь верхового болота – 1722 га. Целью работы было установить влияние метеорологических факторов и уничтожения осушительных канав на гидрологический режим верхового болота. Исходным материалом послужили данные о динамике уровня грунтовых вод за последние 22 года на в 1907 г. осушенных и в 1999 г. вновь затопленных площадях заповедника с болотными почвами. Контрольными площадями послужили нетронутые осушением участки болота, выделенные в центральной части заповедника, где преобладают сообщества пушицы и белого мха (Eriophorum vaginatum – Sphagnum spp.) с низкорослой сосной. Выявлено, что за 7-летний период, прошедший после уничтожения в 1999 г. осушительных канав глубиной 0,9–1,2 м, уровень грунтовых вод на приканавной полосе, равной 980 м, повысился в среднем на 9,8–12,2 см по сравнению с контрольным уровнем. Восстановление уровня грунтовых вод (до контрольного уровня) после уничтожения канав на экстенсивно осушенных площадях происходит спустя 4 года, а на интенсивно осушенных площадях – спустя 12 лет. Установлено, что на потепление климата, т. е. на повышение годовых температур, сильнее реагируют грунтовые воды осушенных болот, чем неосушенных. Ключевые слова: уровень грунтовых вод, уничтожение канав, гидрология, метеорологические факторы, болотo. First Published Online: 14 Oct 2010